Integrating Indigenous Knowledge Systems into Environmental Education in Nigeria: A Pathway to Sustainable Development - Ulayi, Agnes Ingiagar; Omang, Theresa Nkim (Indonesian Journal of Educational Studies, 2024)
Environmental education in Nigeria has largely followed Western models, often overlooking the rich indigenous knowledge systems (IKS) that have sustained local ecosystems for generations. This paper argues for the deliberate integration of IKS into Nigeria’s environmental education framework as a pathway to fostering sustainable development. Through a critical theoretical analysis, the study explores how indigenous ecological practices, traditional conservation ethics, and community-based environmental stewardship can enhance formal education curricula. The paper highlights the gaps in current environmental education policies and proposes a culturally responsive approach that bridges scientific and indigenous perspectives. By drawing on global examples and local case studies, it underscores the potential of IKS to promote deeper ecological awareness, strengthen community engagement, and support Nigeria’s sustainability goals. The study concludes with recommendations for policymakers, educators, and stakeholders to adopt inclusive strategies that recognize and valorize indigenous knowledge in environmental learning